Obstructive Sleep Apnea Is Associated with an Increased Risk of Developing Gastroesophageal Reflux Disease and Its Complications - Xiaoliang Wang; Zachary Wright; Jiayan Wang; Gengqing Song (MDPI AG, 2023)
Patients with obstructive sleep apnea (OSA) commonly report gastroesophageal reflux disease (GERD) symptoms, and limited data suggest a relationship between OSA and GERD-related complications. To investigate this association, we performed a population-based analysis using National Inpatient Sample (NIS) data for 7,159,694 patients. After adjusting for risk factors, OSA patients had a significantly higher incidence of GERD (32.3%) compared to those without OSA (15.0%, p < 0.01). OSA patients also had a higher risk of developing GERD-related complications, including non-erosive esophagitis, erosive esophagitis, esophageal stricture, and Barrett's esophagus with and without dysplasia. Therefore, our results emphasize the importance of early detection and management of GERD and its complications in patients with OSA, particularly those with additional risk factors such as obesity and smoking.